Analisis kinerja karyawan yang dipengaruhi oleh Kepemimpinan, kompensasi, dan Budaya organisasi - Fajar Samodro; Aris Budiono (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This research aims to assess the effectiveness of employee treatment by managing leadership, compensation, and organizational culture, which is expected to improve employee performance. Research data was developed using a Likert scale. Research data was obtained from 100 respondents, not including the 20 respondents intended for validity and reliability testing. We use quantitative methods with multiple linear regression. The IBM SPSS 24 statistical application was used for statistical calculations. This research shows that leadership and compensation variables do not partially influence employee performance, but organizational culture variables have a significant influence on employee performance